Evaluation of Surgical Duration When Preparing the Implant Bed Using the Single Drilling Protocol (Clinical Study) - بشر, عدي; علي خليل (Latakia University Journal -Medical Sciences Series, 2024)
Research objectives: The study aims to assess the efficacy of the single drilling protocol in the success of dental implants, comparing them with the gradual drilling protocol (traditional method). And it will evaluate the duration of surgical procedures. Materials and Methods: A comparative study was conducted on 24 patients visiting the Department of Oral and Maxillofacial Surgery at Tishreen University Hospital and the Department of Oral and Maxillofacial Surgery at the Faculty of Dentistry at Tishreen University. The sample was divided into two groups: 12 Treated using the gradual drilling protocol 12 Treated using the gradual drilling protocol The study utilized a split-mouth method, with patients who had lost a minimum of two teeth being selected for the research. This involved applying the conventional drilling protocol to one implant and the gradual drilling protocol to another to control variables as much as possible. The Results: The success rate of the implants was 100%. The average working time in the single drilling protocol was 21.33±4.03 compared to 43.25±4.2 in the gradual drilling protocol. Conclusions: Within the limits of this study, we determined that the single drilling protocol is a safe and effective method for achieving successful dental implants when compared to the gradual drilling protocol. Additionally, it plays a crucial role in decreasing surgical time.